2016
DOI: 10.1099/ijsem.0.000712
|View full text |Cite
|
Sign up to set email alerts
|

Group 16SrXI phytoplasma strains, including subgroup 16SrXI-B and a new subgroup, 16SrXI-D, are associated with sugar cane white leaf

Abstract: Sugar cane white leaf (SCWL) is a serious disease caused by phytoplasmas. In this study, we performed nested PCR with phytoplasma universal primer pairs (P1/P7 and R16F2n/R16R2) for the 16S rRNA gene to detect SCWL phytoplasmas in 31 SCWL samples collected from Baoshan and Lincang, Yunnan, China. We cloned and sequenced the nested PCR products, revealing that the 16S rRNA gene sequences from 31 SCWL samples were all 1247 bp in length and shared more than 99 % nucleotide sequence similarity with the 16S rRNA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Phytoplasmas have been found associated with hundreds of plant diseases (Bertaccini, 2007; Firrao, Garciachapa, & Marzachi, 2007; Maejima, Oshima, & Namba, 2014). Phytoplasmas of different subgroups infecting same plant species have been widely reported, for example the occurrence of 16SrXI‐B and ‐D on sugar cane (Zhang et al., 2016), or several subgroups of 16SrII infect cactus (Cai, Wei, Davis, Chen, & Zhao, 2008). Besides, mixed infection of different groups was observed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplasmas have been found associated with hundreds of plant diseases (Bertaccini, 2007; Firrao, Garciachapa, & Marzachi, 2007; Maejima, Oshima, & Namba, 2014). Phytoplasmas of different subgroups infecting same plant species have been widely reported, for example the occurrence of 16SrXI‐B and ‐D on sugar cane (Zhang et al., 2016), or several subgroups of 16SrII infect cactus (Cai, Wei, Davis, Chen, & Zhao, 2008). Besides, mixed infection of different groups was observed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Che et al (2009) first discovered the existence of 16SrV phytoplasma in naturally infected periwinkle. Zhang et al (2016) analyzed SCWL phytoplasmas in Yunnan, which showed that SCWL is caused by phytoplasmas from group 16SrXI, including subgroup 16SrXI-B and a new subgroup, 16SrXI-D.…”
Section: Phytoplasma Diseases Distribution and Diversity Infecting Di...mentioning
confidence: 99%
“…The phytoplasma isolates associated with SCWL and SCGS belong to the 16SrXI group based on the high similarity of their 16S rRNA gene sequences (Viswanathan et al, 2011 ; Abeysinghe et al, 2016 ). The group 16SrXI includes the subgroups 16SrXI-B, 16SrXI-D, and 16SrXI-F (Zhang et al, 2016 ; Yadav et al, 2017 ). In 2020, the draft SCGS phytoplasma genome was published (Kirdat et al, 2020 ), and based on its analysis, the phytoplasma isolates associated with SCGS have been classified as a novel taxon “ Candidatus Phytoplasma sacchari” (Kirdat et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%